Desain Pembelajaran Berdiferensiasi Materi Peluang pada Siswa SMPN 18 Kota Kupang - Sudin, Ansgarius Arnoldi; Ekowati, Christine K.; Nada, Yohanes H. (Universitas Nusa Cendana, 2025)
This research is motivated by the implementation of differentiated learning as part of the implementation of the independent curriculum has not been implemented evenly at the educational level, one of which is at SMPN 18 Kota Kupang. In response to this, the researcher wanted to produce a differentiated learning design as part of the independent curriculum, especially on opportunity material. The method used by researchers is design research, which includes 3 stages, preparing for the experiments, the designs experiment and retrospective analysis. The data collection techniques used by researchers are tests (diagnostic and summative assessments), observations and interviews. Data analysis in this study used descriptive qualitative data obtained from observations and interviews, while quantitative data was obtained from the assessment results. This research produces differentiated learning design on chance material. The results showed that the learning design applied by the researcher was effective in helping students in improving student's understanding.